2015
DOI: 10.1124/jpet.115.224212
|View full text |Cite
|
Sign up to set email alerts
|

Translational Pharmacodynamics of Calcitonin Gene-Related Peptide Monoclonal Antibody LY2951742 in a Capsaicin-Induced Dermal Blood Flow Model

Abstract: LY2951742, a monoclonal antibody targeting calcitonin generelated peptide (CGRP), is being developed for migraine prevention and osteoarthritis pain. To support the clinical development of LY2951742, capsaicin-induced dermal blood flow (DBF) was used as a target engagement biomarker to assess CGRP activity in nonhuman primates and healthy volunteers. Inhibition of capsaicin-induced DBF in nonhuman primates, measured with laser Doppler imaging, was dose dependent and sustained for at least 29 days after a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 28 publications
2
66
0
3
Order By: Relevance
“…168 Oral administration of the CGRP antagonist telcagepant and injection of the humanized monoclonal CGRP antibody galcanezumab (LY2951742) both blocked capsaicin-induced increases in dermal blood flow, as measured by laser Doppler perfusion imaging in healthy human subjects. 168,183 Taken together, these observations all support the contention that CGRP is the major mediator of neurogenic dilator responses arising from the activation of sensory nerves in humans. 81 This situation contrasts with the rat, where these neuropeptides produce not only vasodilation and plasma protein extravasation but also histamine release and mast cell degranulation.…”
Section: Peripheral Sensitization and The Role Of Calcitonin Gene–supporting
confidence: 52%
“…168 Oral administration of the CGRP antagonist telcagepant and injection of the humanized monoclonal CGRP antibody galcanezumab (LY2951742) both blocked capsaicin-induced increases in dermal blood flow, as measured by laser Doppler perfusion imaging in healthy human subjects. 168,183 Taken together, these observations all support the contention that CGRP is the major mediator of neurogenic dilator responses arising from the activation of sensory nerves in humans. 81 This situation contrasts with the rat, where these neuropeptides produce not only vasodilation and plasma protein extravasation but also histamine release and mast cell degranulation.…”
Section: Peripheral Sensitization and The Role Of Calcitonin Gene–supporting
confidence: 52%
“…Sinclair et al [118] demonstrated reduced increase in dermal blood flow after topical capsaicin application in the forearm of healthy volunteers who were pretreated with CGRP antagonist (telcagepant). The degree of inhibition in capsaicin-induced dermal blood flow was shown to be increased with higher LY2951742, CGRP monoclonal antibody, plasma concentrations suggesting dose–response relationship [119]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that LY2951742 blocked most of the CGRP-induced peripheral vasodilation [21] suggests that antibodies against CGRP or its receptor would wipe out the entire endogenous CGRP system for at least several weeks. The question we discuss here is, although abolishing the effects of CGRP might be beneficial by preventing migraine attacks, could this also have harmful effects?…”
Section: Trendsmentioning
confidence: 96%